Salary standardization ; Media credibility ; Sigaw ng Penpen [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Tackles government employees protest against SSL and an interview with Rep. Rodolfo Andaya, SSL author; media's credibility as a source of news focusing on SWS survey and Penpen with its pop music using purely contemporary Filipino neo-ethnic rock concept of music.